Semi-Active Magnetorheological Damper Device for Chatter Mitigation during Milling of Thin-Floor Components - Santiago Daniel Puma-Araujo; Daniel Olvera-Trejo; Oscar Martínez-Romero; Gorka Urbikain; Alex Elías-Zúñiga; Luis Norberto López de Lacalle (Applied Sciences, 2020)
The productivity during the machining of thin-floor components is limited due to unstable vibrations, which lead to poor surface quality and part rejection at the last stage of the manufacturing process. In this article, a semi-active magnetorheological damper device is designed in order to suppress chatter conditions during the milling operations of thin-floor components. To validate the performance of the magnetorheological (MR) damper device, a 1 degree of freedom experimental setup was designed to mimic the machining of thin-floor components and then, the stability boundaries were computed using the Enhance Multistage Homotopy Perturbation Method (EMHPM) together with a novel cutting force model in which the bull-nose end mill is discretized in disks. It was found that the predicted EMHPM stability lobes of the cantilever beam closely follow experimental data. The end of the paper shows that the usage of the MR damper device modifies the stability boundaries with a productivity increase by a factor of at least 3.